2ν double beta decay within the relativistic QRPA - De Conti, Cláudio [UNESP]; Krmpotić, Francisco; Carlson, Brett Vern (My University, 2011)
We perform a self-consistent relativistic QRPA (RQRPA) calculation of 2νββ-decay based on relativistic BCS (RBCS) mean field theory results for odd-odd intermediate nuclei 48Sc, 76As, 82Br, 100Tc, 128I, and 130I. The RBCS equations that resemble the non-relativistic ones are constructed from a Dirac-Gorkov variational functional. We use the parameter set NL1 for the σ, ω and ρ mesons. The RQRPA equations are solved for the residual π +ρ interaction by employing the same parameters used in the RBCS for the latter meson, and experimental values for the pion and nucleon. The RQRPA results for the 2νββ matrix elements are similar to those obtained within the QRPA and the shell model.